2021
DOI: 10.4236/ojmh.2021.113004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land Use and Land Cover Changes on Surface Runoff and Sediment Yield in the Little Ruaha River Catchment

Abstract: Little Ruaha River catchment (6370 Km 2 ) in the Southern Agricultural Growth Corridor of Tanzania (SAGCOT), is one of the country's most significant waterways due to its ecological composition and economic value. Regardless of its ecological and economical value, the regional hydrologic condition has been tremendously affected due to land uses alteration, influenced by different socio-economic factors. This study aimed to understand the associated impacts of the present Land Use Land Cover (LULC) change on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Major towns within the basin rely on surface water for domestic water use, which is largely supplied by the Ghana Water Company Limited and Community Water and Sanitation Agency, while almost all rural communities rely solely on groundwater as their source of drinking water as other studies in other countries according to [41] revealed similar use patterns. With some uses relying on the availability of streamflow which is impacted by climate variability and change [42].…”
Section: Study Areamentioning
confidence: 83%
“…Major towns within the basin rely on surface water for domestic water use, which is largely supplied by the Ghana Water Company Limited and Community Water and Sanitation Agency, while almost all rural communities rely solely on groundwater as their source of drinking water as other studies in other countries according to [41] revealed similar use patterns. With some uses relying on the availability of streamflow which is impacted by climate variability and change [42].…”
Section: Study Areamentioning
confidence: 83%
“…Calculating and estimating flood and runoff volume is the best result for enhancement planer and management (Bayazıt et al, 2021). Chilagane et al (2021) recommended that planning LU in the Little Ruaha River catchment (6370 Km 2 ) in the Southern Agricultural Growth Corridor of Tanzania, should be management agriculture practices.…”
Section: Resultsmentioning
confidence: 99%
“…This shows the response of land use changes to water balance and other water resource components depends on the characteristics of hydrological response units (HRUs) [ 13 ]. Indeed, the patterns of the hydrological cycle depend mainly on the intensity of rainfall, the magnitudes of evapotranspiration, and the behavior of LULC, plus the progress of climate change [ 14 ].…”
Section: Introductionmentioning
confidence: 99%